Explosive blasting bead, coat and inner core formula prepared by reverse balling method and process of explosive blasting bead, coat and inner core formula
By using a combination of chitosan and sodium tripolyphosphate, the blast beads were prepared by reverse ball formation method and cured in a cross-linking bath of sodium tripolyphosphate, which solved the problems of low strength and poor stability of the shell of the traditional blast beads, and achieved higher hardness, blast feeling and stability.
Patent Information
- Application Number
- CN202411782813.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The shell of traditional burst beads has low mechanical strength and poor stability, which leads to prone to rupture in desserts such as milk tea, shortening the optimal drinking time.
Chitosan is used as the outer coating material, and the inner core solution containing sodium tripolyphosphate is dropped into the chitosan solution by reverse ball formation method to form a strong gel with a thicker film and cured in a cross-linking bath of sodium tripolyphosphate.
It significantly improves the hardness, explosive feeling and stability of the explosive beads, extends the optimal drinking time, and simplifies the preparation process, with a wide range of applications.
Smart Images

Figure CN119523080A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food processing, and relates to a novel preparation method and application of popping beads and passion fruit juice popping beads; in particular, to popping beads prepared by a reverse spheronization method, a coating and an inner core formulation thereof, and a preparation process thereof. Background Art
[0002] With the improvement of people's living standards. A new dessert ingredient - popping beads is favored by consumers. Popping beads are a spherical capsule with a shell-core structure. It uses special technology to wrap the inner core liquid with fluidity such as sweeteners and fruit juice in the outer shell film. After being squeezed, the outer film breaks and the inner core solution overflows, with a peculiar taste. The existing popping beads have a variety of flavors, including lychee, mango, grape, coconut, chocolate, etc.; popping beads have a wide range of application scenarios. They can not only be used in milk tea, but also added to yogurt, jelly and other desserts to increase their taste characteristics.
[0003] The traditional method of preparing popping beads is mainly to use sodium alginate to react with divalent metal ions such as calcium to generate sodium alginate gel. The raw materials usually used are sodium alginate, calcium solution and fruit juice. Sodium alginate and fruit juice are mixed and dripped into a calcium ion solution, and then boiled and cooled to make it. Chinese invention patent CN114586953A discloses a method for preparing popping beads with natural aloe grains embedded therein, which comprises adding aloe grain juice to an aqueous solution containing a thickener and a stabilizer and mixing them uniformly to obtain an inner core solution, slowly dripping the obtained inner core solution into an aqueous solution containing calcium salt, scooping it out and placing it in a calcium gluconate solution to obtain popping beads with natural aloe grains embedded therein; CN105325829A provides a method for preparing popping beads with active probiotics, which comprises uniformly mixing sodium alginate and probiotics to form a mother liquor of popping beads, then dripping the mother liquor into a solution containing calcium ions, filtering out after soaking, and washing with water to obtain the popping beads; however, the preparation of the above popping beads all adopts a forward spheroidization method, i.e. dripping a sodium alginate colloidal solution into an aqueous solution containing calcium ions, which method has a thin shell and low mechanical strength due to the obstruction of diffusion of calcium ions in a high-viscosity sodium alginate solution, and is easily broken when added to desserts such as milk tea, thereby shortening the optimal drinking time.
[0004] Chitosan is the only natural alkaline polysaccharide with low price and abundant sources. Chitosan not only has excellent biocompatibility, biodegradability and bioadhesion, but also has been confirmed by studies to have good probiotic properties. Its excellent functional properties make chitosan widely used in food, medicine, chemical industry and other fields. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a new method for preparing popping beads with chitosan as the wall material, which is simple in process, good in chewiness, strong in popping feeling and stable, and is an extension and development of the current popping beads preparation technology.
[0006] The invention uses chitosan as the wall material, adds sodium tripolyphosphate to a solution containing a sweetener and a thickener and mixes them evenly to form an inner core solution, and drips the mixed inner core solution into the chitosan solution by a reverse spheronization method to obtain a popping bead product. The method has a simple preparation process and a wide range of applications, and no related methods have been reported.
[0007] The present invention is specifically implemented through the following technical solutions:
[0008] The invention discloses a kind of explosive bead prepared by reverse ball forming method, comprising an outer coating of the explosive bead and an inner core of the explosive bead, wherein the outer coating raw material is selected from chitosan, wherein the mass concentration of the chitosan is 1% to 3%.
[0009] The raw materials of the inner core include: white sugar, xanthan gum, guar gum, fructose syrup, potassium sorbate; further, the raw materials of the inner core also include sodium tripolyphosphate.
[0010] The explosive beads of the present invention are characterized in that the components in the solution of the explosive bead core have a mass ratio of: 2 to 6 parts of white sugar,
[0011] 0.1 to 0.5 parts of xanthan gum,
[0012] 0.5 to 1 part of guar gum,
[0013] 20 to 30 parts of fructose syrup,
[0014] Potassium sorbate 0.1 to 0.3 parts,
[0015] Sodium tripolyphosphate 0.1 to 5 parts,
[0016] 60-70 parts of distilled water.
[0017] The above-mentioned formula of the inner core solution of the popping beads may also include juice, and the mass proportion of the juice is 0 to 20 parts. Among them, the types of juice may include but are not limited to: passion fruit concentrated juice, strawberry concentrated juice, blueberry concentrated juice, lychee concentrated juice, mango concentrated juice, grape concentrated juice, coconut concentrated juice, and a mixture of one or more of other concentrated juices that can be used as beverages. Passion fruit concentrated juice is preferred. Chocolate can also be added to the juice, or chocolate of a certain form or concentration can be selected as a substitute.
[0018] The method for making popping beads of the present invention comprises the following steps:
[0019] (1) Add white sugar, xanthan gum, guar gum, fructose syrup, potassium sorbate, and sodium tripolyphosphate to water, heat and stir to obtain an inner core solution;
[0020] (2) dissolving chitosan in acetic acid solution to obtain a 1% to 3% chitosan solution;
[0021] (3) dropping the inner core solution into the chitosan coating solution to obtain explosive beads;
[0022] (4) placing the popping beads obtained in step (3) in a sodium tripolyphosphate solution to obtain solidified popping beads, and washing them to obtain the popping beads.
[0023] Furthermore, the method for preparing the popping bead product of the present invention comprises the following steps:
[0024] (1) Take a certain amount of water, heat it to 50-80° C., add white sugar, xanthan gum, guar gum, and fructose syrup, stir, add potassium sorbate, heat the solution to boiling and keep boiling, cool it to room temperature, add sodium tripolyphosphate, continue stirring, and obtain an inner core solution;
[0025] (2) dissolving chitosan in acetic acid solution, stirring at room temperature for at least 12 hours to obtain a chitosan solution with a mass concentration of 1% to 3%, and ultrasonicating and allowing to stand for 0.5 to 2 hours to obtain a coating solution;
[0026] (3) heating the inner core solution of step (1) and continuously stirring it, and slowly dripping it into the chitosan coating solution to obtain explosive beads;
[0027] (4) placing the explosive beads obtained in step (3) in a sodium tripolyphosphate solution for solidification to obtain the solidified explosive beads, and washing them with distilled water and ethanol respectively.
[0028] Furthermore, the method for preparing the popping bead product of the present invention comprises the following steps:
[0029] (1) Preparation of the explosive bead core solution
[0030] Preparation of the inner core solution: measure a certain amount of distilled water into a beaker, place it on an electromagnetic heating stirrer and heat it. When the temperature rises to 50-80°C, add white sugar, xanthan gum, guar gum and fructose syrup in turn, stir well under heating, and after all the ingredients are completely dissolved, add potassium sorbate and continue stirring for 0.5-2h. Then heat the solution to boiling and keep it for 5-30min. After the solution temperature drops to room temperature, first add passion fruit concentrated juice and then add sodium tripolyphosphate and continue stirring for 0.5-2h to obtain the inner core solution.
[0031] (2) Preparation of the thin shell coating solution of the explosive beads
[0032] Preparation of outer coating solution: prepare a chitosan solution with a mass fraction of 1% to 3%, subject the obtained chitosan solution to ultrasonic treatment, and let it stand for 0.5 to 2 hours to obtain an outer coating solution.
[0033] (3) Preparation of Exploding Beads
[0034] The inner core solution obtained in (1) is continuously stirred on an electromagnetic heating stirrer and its temperature is raised to 50-80° C. The stirred inner core solution is slowly and evenly dripped into the outer coating solution prepared in step 2) using a constant flow pump to obtain preliminary popping beads;
[0035] (4) Fixing, forming and cleaning of popping beads
[0036] The popping beads obtained in (3) are added to a cross-linking bath of sodium tripolyphosphate solution, left to stand for 0.5 to 2 hours, taken out, washed 3 to 5 times with distilled water, and then washed 1 to 3 times with 3 to 6 times the volume of anhydrous ethanol, to obtain the desired popping beads.
[0037] The above method for preparing popping beads can be used to prepare various fruit or chocolate popping beads, such as passion fruit popping beads, lychee popping beads, mango popping beads, grape popping beads, coconut popping beads, and chocolate popping beads. The method is to add corresponding fruit juice, concentrated fruit juice, etc. to step (1) of the above method,
[0038] For example, according to the above method, a method for preparing popping pearls containing passion fruit can be described as follows:
[0039] (1) taking a certain amount of water, heating it to 50-80° C., adding white sugar, xanthan gum, guar gum, and fructose syrup, stirring, adding potassium sorbate, heating the solution to boiling and maintaining the boiling state, cooling it to room temperature, first adding passion fruit concentrated juice, then adding sodium tripolyphosphate, and continuing to stir to obtain an inner core solution;
[0040] (2) dissolving chitosan in acetic acid solution, stirring at room temperature for at least 12 hours to obtain a chitosan solution with a mass concentration of 1% to 3%, ultrasonicating, and allowing to stand for 0.5 to 2 hours to obtain a coating solution;
[0041] (3) heating the inner core solution of step (1) and continuously stirring, and slowly dripping it into the chitosan coating solution to obtain explosive beads;
[0042] (4) placing the explosive beads obtained in step (3) in a sodium tripolyphosphate solution for solidification to obtain the solidified explosive beads, and washing them with distilled water and ethanol respectively.
[0043] Furthermore, in the method of making popping beads or juice popping beads, in step (1), the mass ratio of the crosslinking agent sodium tripolyphosphate in the popping bead core solution is 0.5% to 5%, and the boiling state of the solution is maintained for 5 minutes to 30 minutes.
[0044] The method for making popping beads or juice popping beads described above, wherein the viscosity of the chitosan described in step (2) is 100-200 mPa.S. The preparation method of the chitosan solution is: dissolving chitosan with a viscosity of 100-200 mPa.S in 0.5-2% acetic acid, and dissolving it overnight with magnetic stirring. The frequency of the ultrasound described in step (2) is 20 Hz-50 Hz, and the ultrasound time is 10 min-30 min.
[0045] The method for making popping beads or juice popping beads, wherein in step (3), the temperature of the inner core solution after heating is 50-80°C, and the stirring speed of the inner core solution is 100-1000rpm. Step (3) is slowly dripped by a constant flow pump, the inner diameter of the selected constant flow pump tube is 1mm-5mm, and the flow rate of the constant flow pump is 2-20rpm.
[0046] The method for making popping beads or juice popping beads as described above, wherein the mass concentration of sodium tripolyphosphate in step (4) is 0.5% to 5%. The curing time in step (4) is 0.5 to 2 hours. The washing described in step (4) is to wash the popping beads with pure water for 3 to 5 times, and then wash them with 36 times the volume of anhydrous ethanol for 1 to 3 times.
[0047] The invention uses chitosan as the wall material and utilizes the reverse spheronization method to prepare the popping beads and the corresponding popping bead products, which are prepared by the above production method, and the particle size of the obtained popping bead products is 4mm to 10mm. The popping bead products have high hardness, good chewiness, obvious popping feeling and good stability.
[0048] The present invention overcomes several shortcomings of traditional popping beads. The raw materials of the traditional method for preparing popping beads are mostly sodium alginate, calcium carbonate and fruit juice. The shell of the popping beads formed by this method has weak mechanical strength and poor stability, and is not suitable for large-scale food processing. The present invention uses sodium tripolyphosphate as a cross-linking agent and chitosan as the outer coating of the popping beads. The preparation method is simple and easy, and has a wide range of applications. It is a new process for preparing popping bead products. The present invention makes full use of the easy film-forming properties of chitosan, and further solidifies the formed popping beads in a sodium tripolyphosphate cross-linking bath, thereby enhancing the hardness and popping feeling of the popping beads, and significantly improving its palatability and stability as a dessert ingredient.
[0049] Compared with the prior art, the preparation method of the present invention and the resulting explosive beads have the following advantages:
[0050] (1) The present invention uses chitosan as the outer coating of the explosive beads, and uses the reverse spheronization method to drop the inner core solution containing sodium tripolyphosphate into the chitosan outer coating solution. The sodium tripolyphosphate in the droplets quickly diffuses into the chitosan solution, thereby forming a strong gel with a thicker film.
[0051] (2) After the popping beads prepared by the present invention are initially formed, they are further cured in a sodium tripolyphosphate cross-linking bath, and the resulting popping bead products have greater hardness, stronger popping sensation, better stability, and more palatable taste.
[0052] (3) The method for preparing the explosive beads described in the present invention is simple to operate, has relatively low cost, and takes a short operation time. Therefore, the method described in the present invention is easy to realize large-scale production of explosive beads.
[0053] (4) Food raw materials are highly safe and price controllable. The present invention uses chitosan as the wall material, the raw material source is wide, is not restricted by the place of origin, and the processing technology is simple.
[0054] (5) The present invention is suitable for the preparation of popping beads for different beverage juices, has a wide range of applications, and can meet the needs of various food tastes.
[0055] The present invention discloses popping beads prepared by the reverse spheronization method, their outer coating and inner core formulations, and their preparation process. The method uses chitosan solution as the popping bead outer coating solution, and uses a sweetener, a thickener, a cross-linking agent and / or passion fruit juice to prepare the inner core solution of the popping beads, and drips the evenly mixed inner core solution into the chitosan outer coating solution drop by drop by the reverse spheronization method. The method uses chitosan as the wall material, and undergoes a sodium tripolyphosphate cross-linking bath and secondary curing, which can significantly improve the nutritional characteristics and stability of the popping bead products. The processing method of the present invention is simple and has wide applicability. The popping bead products have uniform particle size, uniform color, good stability, good chewiness, and a strong popping feeling, which improves their palatability when used as food ingredients.
[0056] The popping bead product and the method thereof of the present invention can be used for food preparation, especially desserts.
[0057] Instruction Manual
[0058] Figure 1 This is a diagram of the particle size of the explosive beads prepared in Example 1;
[0059] Figure 2 The rupture force and fragility results of the explosive beads prepared in Examples 1, 2, and 3 under the refined TPA mode;
[0060] Figure 3 This is a particle size diagram of passion fruit juice popping beads prepared in Example 4;
[0061] Figure 4The rupture force and brittleness results of the passion fruit juice popping beads prepared in Examples 4, 5, and 6 under the refined TPA mode. DETAILED DESCRIPTION
[0062] The present invention is further described below in conjunction with specific implementation cases and drawings, but the implementation methods of the present invention are not limited to these embodiments, and any changes or equivalent substitutions that do not deviate from the concept of the present invention are included in the protection scope of the present invention.
[0063] In the embodiment of the present invention, white sugar and fructose syrup produced by Yichang Bodi Trading Co., Ltd., xanthan gum, guar gum, potassium sorbate, sodium tripolyphosphate produced by Sinopharm Group Chemical Reagent Co., Ltd., chitosan produced by McLean Company and passion fruit concentrated juice are used to prepare the popping bead products. The particle size of the popping bead products is measured by a vernier caliper, and the TA-XT.PLUS texture analyzer of the British Stable Micro System Company is used to analyze the texture of the prepared popping bead products in two modes, TPA and refined TPA. Among them, the TPA mode mainly simulates human chewing through two compression experiments, and accurately quantifies the hardness, elasticity, cohesion, adhesion and chewiness of the sample. The specific test conditions are as follows: 3 prepared popping bead samples are randomly selected and placed under the p / 36R probe, and the pre-test speed, test speed and post-test speed are all 1mm / s, the trigger force is 5g, and the compression deformation is 50%. The refineTPA mode evaluates important indicators such as the rupture force and brittleness of the prepared explosive beads through a single pressure and a puncture test. Specifically, a prepared explosive bead is randomly selected and placed directly under the p / 50 probe. The pre-test speed, test speed, and post-test speed are all 5mm / s, the trigger force is 5g, the first pressure compression deformation is 50%, and the second compression deformation is 80%.
[0064] Example 1 A method for preparing explosive beads (1% chitosan solution)
[0065] (1) Preparation of the inner core solution of the explosive beads. Preparation of the inner core solution: Measure 169.88 mL of distilled water into a beaker and heat it on an electromagnetic heating stirrer. When the temperature rises to 60°C, add 12.5 g of white sugar, 1 g of xanthan gum, 1.25 g of guar gum and 62.5 g of fructose syrup in sequence. Stir well under heating. After all the ingredients are completely dissolved, add 0.375 g of potassium sorbate and continue stirring for 0.5 h. Heat the solution to a boiling state and keep the solution boiling for 10 min. After the solution temperature drops to room temperature, add 2.5 g of sodium tripolyphosphate and continue stirring for 0.5 h to obtain the inner core solution.
[0066] (2) Preparation of the thin shell coating solution of the explosive beads. Preparation of the coating solution:
[0067] 1 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 100 mL of 1% acetic acid solution and stirred overnight to fully dissolve it to obtain a 1% chitosan solution. The chitosan solution was ultrasonically treated at 40 Hz for 5 min to remove bubbles, and then the solution was allowed to stand for 0.5 h to obtain a coating solution.
[0068] (3) Preparation of explosive beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 10 rpm using a constant flow pump to obtain preliminary explosive beads;
[0069] (4) Curing and cleaning of the popping beads. The popping beads obtained in step (3) are added to a cross-linking bath of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead products.
[0070] Example 2 A method for preparing explosive beads (2% chitosan solution)
[0071] (1) Preparation of the inner core solution of the explosive beads. Preparation of the inner core solution: Measure 169.88 mL of distilled water into a beaker and heat it on an electromagnetic heating stirrer. When the temperature rises to 60°C, add 12.5 g of white sugar, 1 g of xanthan gum, 1.25 g of guar gum and 62.5 g of fructose syrup in sequence. Stir well under heating. After all the ingredients are completely dissolved, add 0.375 g of potassium sorbate and continue stirring for 0.5 h. Heat the solution to a boiling state and keep the solution boiling for 10 min. After the solution temperature drops to room temperature, add 2.5 g of sodium tripolyphosphate and continue stirring for 0.5 h to obtain the inner core solution.
[0072] (2) Preparation of the thin shell coating solution of the explosive beads. Preparation of the coating solution:
[0073] 6 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 300 mL of 1% acetic acid solution and stirred overnight to fully dissolve it to obtain a 2% chitosan solution. The chitosan solution was ultrasonically treated at 40 Hz for 5 min to remove bubbles, and then the solution was allowed to stand for 0.5 h to obtain a coating solution.
[0074] (3) Preparation of explosive beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 10 rpm using a constant flow pump to obtain preliminary explosive beads;
[0075] (4) Curing and cleaning of the popping beads. The popping beads obtained in step (3) are added to a cross-linking bath of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead products.
[0076] Example 3 A method for preparing explosive beads (3% chitosan solution)
[0077] (1) Preparation of the inner core solution of the explosive beads. Preparation of the inner core solution: Measure 169.88 mL of distilled water into a beaker and heat it on an electromagnetic heating stirrer. When the temperature rises to 60°C, add 12.5 g of white sugar, 1 g of xanthan gum, 1.25 g of guar gum and 62.5 g of fructose syrup in sequence. Stir well under heating. After all the ingredients are completely dissolved, add 0.375 g of potassium sorbate and continue stirring for 0.5 h. Heat the solution to boiling and keep the solution boiling for 10 min. After the solution temperature drops to room temperature, add 2.5 g of sodium tripolyphosphate and continue stirring for 0.5 h to obtain the inner core solution.
[0078] (2) Preparation of the thin shell coating solution of the explosive beads. Preparation of the coating solution:
[0079] 9 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 300 mL of 1% acetic acid solution and stirred overnight to fully dissolve it to obtain a 3% chitosan solution. The chitosan solution was ultrasonically treated at 40 Hz for 5 min to remove bubbles, and then the solution was allowed to stand for 0.5 h to obtain a coating solution.
[0080] (3) Preparation of explosive beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 10 rpm using a constant flow pump to obtain preliminary explosive beads;
[0081] (4) Curing and cleaning of the popping beads. The popping beads obtained in step (3) are added to a cross-linking bath of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead products.
[0082] Example 4 Preparation method of explosive beads of passion fruit juice (1% chitosan solution)
[0083] (1) Preparation of the inner solution of passion fruit juice popping beads. Preparation of the inner solution: Measure 67.95 mL of distilled water into a beaker and place it on an electromagnetic heating stirrer to heat it. When the temperature rises to 60°C, add 5% white sugar, 0.4% xanthan gum, 0.5% guar gum and 25% fructose syrup in turn. Stir these components at 600 rpm until they are completely dissolved. Then add 0.15% potassium sorbate by weight. Heat the solution to boiling while stirring. Keep boiling for 10 minutes. After the solution temperature drops to room temperature, add 10 g of passion fruit concentrated juice. After mixing evenly, add 1 g of sodium tripolyphosphate and continue stirring for 0.5 h to obtain the inner solution.
[0084] (2) Preparation of passion fruit juice popping pearl thin shell coating solution. Preparation of coating solution: 3 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 300 mL of 1% acetic acid solution, stirred at room temperature for 12 h to fully dissolve it, and a 1% chitosan solution was obtained. The chitosan solution was ultrasonically treated at 40 Hz for 15 min to remove bubbles therein, and then the solution was allowed to stand for 1 h to obtain a coating solution.
[0085] (3) Preparation of passion fruit juice popping beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer, and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 5 rpm using a constant flow pump to obtain preliminary popping beads.
[0086] (4) Curing and cleaning of passion fruit juice popping beads. The popping beads obtained in step (3) were added to a cross-linking bath of 500 mL of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead product.
[0087] Example 5 Preparation method of popping beads of passion fruit juice (2% chitosan solution)
[0088] (1) Preparation of the inner solution of passion fruit juice popping beads. Preparation of the inner solution: Measure 67.95 mL of distilled water into a beaker and place it on an electromagnetic heating stirrer to heat it. When the temperature rises to 60°C, add 5% white sugar, 0.4% xanthan gum, 0.5% guar gum and 25% fructose syrup in sequence. Stir these components at 600 rpm until they are completely dissolved. Then add 0.15% potassium sorbate by weight. Heat the solution to boiling while stirring. Keep boiling for 10 minutes. After the solution temperature drops to room temperature, add 10 g of passion fruit concentrated juice. After mixing evenly, add 1 g of sodium tripolyphosphate and continue stirring for 0.5 h to obtain the inner solution.
[0089] (2) Preparation of passion fruit juice popping pearl thin shell coating solution. Preparation of coating solution: 6 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 300 mL of 1% acetic acid solution, and stirred at room temperature for 12 h to fully dissolve it to obtain a 2% chitosan solution. The obtained chitosan solution was ultrasonically treated at 40 Hz for 15 min to remove bubbles therein, and then the solution was allowed to stand for 1 h to obtain a coating solution.
[0090] (3) Preparation of passion fruit juice popping beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer, and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 5 rpm using a constant flow pump to obtain preliminary popping beads.
[0091] (4) Curing and cleaning of passion fruit juice popping beads. The popping beads obtained in step (3) were added to a cross-linking bath of 500 mL of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead product.
[0092] Example 6 Preparation method of explosive beads of passion fruit juice (3% chitosan solution)
[0093] (1) Preparation of the inner solution of passion fruit juice popping beads. Preparation of the inner solution: 67.95 mL of distilled water was measured and placed in a beaker, and the beaker was placed on an electromagnetic heating stirrer for heating. When the temperature rose to 60°C, 5% by weight of white sugar, 0.4% by weight of xanthan gum, 0.5% by weight of guar gum, and 25% by weight of high fructose corn syrup were added thereto in sequence. These components were continuously stirred at 600 rpm until they were completely dissolved, and then 0.15% by weight of potassium sorbate was added. The solution was heated to a boiling state while stirring, and the boiling state was maintained for 10 minutes. After the solution temperature dropped to room temperature, 10 g of passion fruit concentrated juice was added thereto. After mixing evenly, 1 g of sodium tripolyphosphate was added thereto, and stirring was continued for 0.5 h to obtain the inner solution.
[0094] (2) Preparation of passion fruit juice popping pearl thin shell coating solution. Preparation of coating solution: 9 g of chitosan with a viscosity of 100-200 mPa.s was dissolved in 300 mL of 1% acetic acid solution, stirred at room temperature for 12 h to fully dissolve it, and a 3% chitosan solution was obtained. The chitosan solution was ultrasonically treated at 40 Hz for 15 min to remove bubbles therein, and then the solution was allowed to stand for 1 h to obtain a coating solution.
[0095] (3) Preparation of passion fruit juice popping beads. The inner core solution obtained in step (1) was continuously stirred on an electromagnetic heating stirrer, and its temperature was raised to 60°C. The stirred inner core solution was slowly and evenly dripped into the outer coating solution prepared in step (2) at a speed of 5 rpm using a constant flow pump to obtain preliminary popping beads.
[0096] (4) Curing and cleaning of passion fruit juice popping beads. The popping beads obtained in step (3) were added to a cross-linking bath of 500 mL of sodium tripolyphosphate solution (1%, w / v), left to stand for 1 hour, and then taken out and washed with distilled water for 3 times and then with 3 times the volume of anhydrous ethanol for 3 times, respectively, to obtain the desired popping bead product.
[0097] Example 7 Determination of particle size of popping beads
[0098] Six popping beads prepared in step (4) of the preparation example after solidification and cleaning were randomly selected, and their surface moisture was wiped dry. The particle size was measured using a vernier caliper, and the two jaws of the vernier caliper were fixed on both sides of the popping beads to measure the particle size.
[0099] Figure 1 This is a picture of the particle size of the explosive beads prepared in Example 1. It can be seen from the picture that the explosive beads prepared in the above example have a transparent shell, uniform color, moderate size, and their particle size does not change significantly with the increase of chitosan concentration, and the average particle size is 6.3 mm.
[0100] Example 8 Determination of the texture of the popping beads - hardness, elasticity, etc.
[0101] Three popping beads that were cured and cleaned in step (4) of the preparation example were randomly selected, their surface moisture was wiped dry, and they were placed on the sample stage of a texture analyzer. The hardness, elasticity, cohesion, adhesiveness, chewiness, rupture force and brittleness of the prepared strawberry juice popping beads were measured and analyzed using the TPA mode and the refined TPA mode, respectively.
[0102] Table 1 shows the hardness, elasticity, cohesiveness, chewiness and resilience of the popping beads of Examples 1, 2 and 3 measured under TPA mode.
[0103] Table 1 Key properties of the popping beads in Examples 1, 2, and 3 under TPA mode
[0104]
[0105] It can be seen from Table 1 that when the concentration of outer shell chitosan is 1%, the hardness of the prepared popping beads is small, the elasticity is poor, and the cohesion, chewiness and recovery are average. As the concentration of outer shell chitosan of the popping beads increases from 1% to 2%, its hardness, elasticity, cohesion, chewiness and recovery are significantly improved, while when the concentration of outer shell chitosan of the popping beads increases from 2% to 3%, its texture indicators including hardness do not change significantly.
[0106] Example 9 Determination of the texture of the popping beads 2 - rupture force and brittleness
[0107] To further simulate the popping sensation of the popping beads when eaten, Figure 2 The rupture force and brittleness test results of the popping beads of Examples 1, 2, and 3 measured under the refined TPA mode.
[0108] Depend on Figure 2 It can be seen that when the chitosan concentration of the bursting beads is low (1%), the rupture force (i.e., the bursting feeling) of the bursting beads is very weak, but the brittleness is better; when the concentration of the chitosan coating rises to 2%, the bursting feeling of the bursting beads is significantly improved, and the brittleness increases from 32.48 at 1% to 75.43 at 2%, and when the chitosan concentration continues to increase to 3%, the bursting feeling of the bursting beads decreases to a certain extent, but the brittleness change is not obvious.
[0109] It can be seen from the above texture determination experiment of the popping beads that the present invention adds sodium tripolyphosphate to the inner core solution, and drips the evenly mixed inner core solution drop by drop into the chitosan-containing popping bead coating solution by means of the reverse spheronization method. After preliminary forming, the popping beads are fished out and secondary cured in a sodium tripolyphosphate cross-linking bath to enhance the stability of the popping beads. When the concentration of chitosan in the popping bead coating is 1%, the formed popping beads have a smaller hardness, a weaker popping feeling, and poorer chewiness. When the concentration of chitosan in the popping bead coating is increased from 1% to 2%, the popping feeling and chewiness of the prepared popping beads are significantly enhanced. The texture indicators of the popping beads do not change significantly when the chitosan concentration is further increased. Based on the results of the comprehensive determination of particle size, texture, etc., it can be seen that when the concentration of the chitosan coating is 2%, the texture of the prepared popping bead product is better.
[0110] Example 10 Determination of particle size of passion fruit juice popping beads
[0111] Six passion fruit popping beads that were cured and cleaned in step (4) of the preparation example were randomly selected, and their surface moisture was wiped dry. The particle size was measured using a vernier caliper, and the two jaws of the vernier caliper were fixed to the two sides of the popping beads to measure the particle size.
[0112] Figure 3 The particle size diagram of the passion fruit juice popping beads prepared in Example 4. Compared with the popping beads without beverage juice, the particle size of the popping beads with passion fruit juice did not change significantly (6.0 mm), and with the increase of the concentration of chitosan in the outer coating of the popping beads, the particle size did not change significantly, and the average particle size of the popping beads with passion fruit juice was still 6.3 mm.
[0113] Example 11 Determination of the texture of passion fruit juice popping beads - hardness, elasticity, etc.
[0114] Three passion fruit popping beads that were cured and cleaned in step (4) of the preparation example were randomly selected, and after the surface moisture was wiped dry, they were placed on the sample stage of the texture analyzer, and the hardness, elasticity, cohesion, adhesiveness, chewiness, and rupture force, toughness, and brittleness of the prepared strawberry juice popping beads were measured and analyzed using the TPA mode and the refined TPA mode. The results are shown in Table 2: Hardness, elasticity, cohesion, chewiness, and resilience of passion fruit popping beads in Examples 4, 5, and 6 measured in the TPA mode.
[0115] Table 2 Key properties of passion fruit popping beads in Examples 4, 5, and 6 measured under TPA mode
[0116]
[0117] It can be seen from Table 2 that, unlike the popping beads prepared without adding beverage juice, the hardness, elasticity, cohesion, chewiness and resilience of the popping beads prepared after adding passion fruit juice gradually increase with the increase of chitosan concentration in the outer coating of the popping beads. The hardness increases from 151.60 at a chitosan concentration of 1% to 300.24 at a chitosan concentration of 3%, and correspondingly, the chewiness also increases from 40.64 at a chitosan concentration of 1% to 142.79% at a chitosan concentration of 3%.
[0118] Example 12 Determination of the texture of passion fruit juice popping beads II - rupture force and brittleness
[0119] In order to further simulate the popping sensation of passion fruit popping beads when eaten, Figure 4 These are the rupture force and brittleness test results of passion fruit popping beads of Examples 4, 5 and 6 measured under the refined TPA mode.
[0120] Figure 4 The bursting feeling test of the prepared passion fruit juice bursting beads. When the concentration of the chitosan coating of the bursting beads is 1%, the bursting force of the bursting beads is small, the bursting feeling is weak, and the brittleness is 64.61. Increasing the chitosan concentration to 2%, the bursting feeling of the obtained bursting beads is significantly enhanced, and its bursting force and brittleness are 330.93 and 74.76 respectively; continuing to increase the chitosan concentration to 3%, its bursting force and brittleness do not change much. Comprehensively considering the hardness, elasticity, cohesion, chewiness and resilience, it can be seen that the taste of the bursting beads prepared after adding beverage concentrate is optimal when the chitosan concentration is 3%.
[0121] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or the technical features can be replaced by equivalents, without departing from the purpose of the technical solution of the present invention, and all should be included in the protection scope of the claims of the present invention.
Claims
1. A popping bead prepared by a reverse balling method, comprising a popping bead outer coat and a popping bead inner core, characterized in that The outer coating material is chitosan.
2. The explosive beads according to claim 1, wherein the mass concentration of chitosan is 1% to 3%.
3. The popping beads according to claim 2, characterized in that The raw materials of the inner core include: white sugar, xanthan gum, guar gum, fructose syrup and potassium sorbate.
4. The popping beads according to claim 3, characterized in that The inner core material also includes sodium tripolyphosphate.
5. The popping beads according to claim 4, characterized in that The mass proportions of the components in the explosive bead core solution are: 2 to 6 parts of white sugar, 0.1 to 0.5 parts of xanthan gum, 0.5 to 1 part of guar gum, 20 to 30 parts of fructose syrup, 0.1 to 0.3 parts of potassium sorbate, 0.1 to 5 parts of sodium tripolyphosphate, and 60-70 parts of distilled water.
6. The popping beads according to claim 5, characterized in that The popping bead core solution may further include fruit juice, with the weight proportion of the fruit juice being 0 to 20 parts.
7. The popping beads as described in claim 6, wherein the juice can be selected from: passion fruit concentrated juice, strawberry concentrated juice, blueberry concentrated juice, lychee concentrated juice, mango concentrated juice, grape concentrated juice, coconut concentrated juice, and a mixture of one or more of the beverage concentrated juices.
8. The popping beads as claimed in claim 7, wherein the juice is selected from passion fruit concentrated juice.
9. The popping beads as claimed in claim 8, wherein the fruit juice can be replaced by chocolate.
10. A method for preparing the popping beads according to claims 1-9, comprising the following steps: (1) Add white sugar, xanthan gum, guar gum, fructose syrup, potassium sorbate, and sodium tripolyphosphate to water, heat and stir to obtain an inner core solution; (2) dissolving chitosan in acetic acid solution to obtain a 1% to 3% chitosan solution; (3) dropping the inner core solution into the chitosan coating solution to obtain explosive beads; (4) placing the popping beads obtained in step (3) in a sodium tripolyphosphate solution to obtain solidified popping beads, and washing them to obtain the popping beads.
11. The method for making popping beads according to claim 10, comprising the following steps: (1) Take a certain amount of water, heat it to 50-80° C., add white sugar, xanthan gum, guar gum, and fructose syrup, stir, add potassium sorbate, heat the solution to boiling and keep boiling, cool it to room temperature, add sodium tripolyphosphate, continue stirring, and obtain an inner core solution; (2) dissolving chitosan in acetic acid solution, stirring at room temperature for at least 12 hours to obtain a chitosan solution with a mass concentration of 1% to 3%, ultrasonicating for 10 to 30 minutes, and letting it stand for 0.52 hours to obtain a coating solution; (3) heating the inner core solution of step (1) and continuously stirring it, and slowly dropping it into the chitosan coating solution to obtain explosive beads; (4) placing the explosive beads obtained in step (3) in a sodium tripolyphosphate solution for solidification to obtain the solidified explosive beads, and washing them with distilled water and ethanol respectively.
12. A method for preparing passion fruit popping beads according to claim 11, characterized in that: (1) taking a certain amount of water, heating it to 50-80° C., adding white sugar, xanthan gum, guar gum, and fructose syrup, stirring, adding potassium sorbate, heating the solution to boiling and maintaining the boiling state, cooling it to room temperature, first adding passion fruit concentrated juice, then adding sodium tripolyphosphate, and continuing to stir to obtain an inner core solution; (2) dissolving chitosan in acetic acid solution, stirring at room temperature for at least 12 hours to obtain a chitosan solution with a mass concentration of 1% to 3%, and ultrasonicating and allowing to stand for 0.5 to 2 hours to obtain a coating solution; (3) heating the inner core solution of step (1) and continuously stirring, and slowly dripping it into the chitosan coating solution to obtain explosive beads; (4) placing the explosive beads obtained in step (3) in a sodium tripolyphosphate solution for solidification to obtain the solidified explosive beads, and washing them with distilled water and ethanol respectively.
13. The method according to claim 11, characterized in that In step (1), the solution is kept in a boiling state for 5 to 30 minutes.
14. The method according to claim 11, characterized in that The viscosity of the chitosan in step (2) is 100-200 mPa.S, and the concentration of the acetic acid solution is 0.5%-2%.
15. The method according to claim 11, characterized in that The frequency of the ultrasound in step (2) is 20 Hz to 50 Hz.
16. The method according to claim 11, characterized in that In step (3), the temperature of the inner core solution after heating is 50-80° C., and the stirring speed of the inner core solution is 100-1000 rpm.
17. The method according to claim 11, characterized in that Step (3) is to slowly drip in via a constant flow pump, wherein the flow rate of the constant flow pump is 2 to 20 rpm.
18. The method according to claim 11, characterized in that The mass concentration of sodium tripolyphosphate in step (4) is 0.5% to 5%.
19. The method according to claim 11, characterized in that The curing time in step (4) is 0.5 to 2 hours.
20. The method of claim 11, wherein: The washing described in step (4) is to wash the popping beads with pure water for 3 to 5 times, and then wash them with 3 to 6 times the volume of anhydrous ethanol for 1 to 3 times.
21. Use of the popping bead product according to claims 1-9 in food preparation, preferably dessert.
Citation Information
Patent Citations
Popping boba, beverage containing same and preparation method of popping boba
CN105325829A
Natural aloe granule embedded blasting bead and preparation method thereof
CN114586953A